Formulation and Physical Stability of Ointment Preparation Ethanol Extract of Piper betle L - Taryono, Ribka Mutiara; Sulastri, Titin; Suwitono, Marvel Reuben (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Betel leaves are commonly used to treat mouth ulcers, eliminate body odor, itching, burns, and vaginal discharge. Inflammation is the body's natural protective response to tissue damage caused by physical trauma, exposure to harmful chemicals, or microbial infection. This study aimed to formulate and evaluate the physical stability of ointment preparations containing ethanol extract of Piper betle L. Three types of ointment bases hydrocarbon, absorption, and water-soluble were developed using 8.67 g of Piper betle extract. The formulations were assessed for organoleptic characteristics, homogeneity, pH, adhesion, spreadability, and viscosity. The extraction process yielded 26.92 g of thick extract (13.5%), with active compounds such as essential oils, alkaloids, flavonoids, tannins, and saponins known for their anti-inflammatory properties. Evaluation results showed that all formulations had a semi-solid consistency, homogeneous texture, and stable color and odor. The pH of all samples was 5, within the safe range for topical use. The water-soluble base exhibited the highest adhesion (6.46 seconds) and spreadability (6.53 cm), while the absorption base exhibited the highest viscosity (8,604 mPa·s). These results indicate that all ointment formulations met the required physical standards and were stable during storage. The ethanol extract of Piper betle L. can therefore be developed as a safe and effective herbal topical anti-inflammatory preparation.